2018
DOI: 10.1111/1467-8500.12266
|View full text |Cite
|
Sign up to set email alerts
|

Feminising Politics to Close the Evidence‐Policy Gap: The Case of Social Policy in Scotland

Abstract: Policy studies suggest that scientists should adopt two strategies to close the 'evidence-policy gap'. First, engage in political debates to help define policy problems and solutions rather than expect the evidence to speak for itself. Second, learn where the action is, form longterm coalitions, and exploit the 'rules of the game' to maximise your influence in complex policy-making systems. Both lessons can prompt major dilemmas, for many actors, about going beyond your expertise and comfort zone when engaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Their identification as feminists committed to advancing women's rights was strong enough to create alliances across party lines and national differences (Locher 2002). Cairney and Rummery (2018) suggest that regular contact between members of the networks helped produce trust and the development of shared aims. One characteristic that many studies identified was the fluidity of the network: women tended to move between the different groupings in the network, for example a policy expert taking up a role at a university or an activist becoming an elected politician.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Their identification as feminists committed to advancing women's rights was strong enough to create alliances across party lines and national differences (Locher 2002). Cairney and Rummery (2018) suggest that regular contact between members of the networks helped produce trust and the development of shared aims. One characteristic that many studies identified was the fluidity of the network: women tended to move between the different groupings in the network, for example a policy expert taking up a role at a university or an activist becoming an elected politician.…”
Section: Contextmentioning
confidence: 99%
“…One characteristic that many studies identified was the fluidity of the network: women tended to move between the different groupings in the network, for example a policy expert taking up a role at a university or an activist becoming an elected politician. Feminist academics often engaged in activism as well as research, although it was less usual to find them moving to formal politics (Cairney and Rummery 2018). Patternotte and Kollman (2013) describe these networks as 'incredibly porous', noting that single actors wore multiple hats and operated, often simultaneously, in multiple arenas.…”
Section: Contextmentioning
confidence: 99%
“…More notably, feminist institutionalism suggests that the ‘rules of the game’ in politics provide unequal access to men and women (Chappell and Waylen, 2013; Kenny, 2007; Lovenduski, 1998; Mackay, 2004). Furthermore, if we combine institutionalist studies with the wider literature on power and knowledge, we find that many women form feminist networks built partly on their experiences of exclusion (Cairney and Rummery, 2018; Woodward, 2004), there is a stronger tendency for women of colour to be abused and threatened in debate (Zevallos, 2017) and erased in intellectual and activism history (Cooper, 2017; Emejulu, 2018), while some forms of knowledge – primarily from the Global South – are marginalised in academic studies and policy debate (Hall and Tandon, 2017; Oliver and Faul, 2018). These imbalances in respect for knowledge claims, and opportunities to communicate or engage, combine with similar types of inequality within the academic profession, in which white men are more likely to be in senior academic positions, published and cited in high ‘impact’ journals, and submitted to the REF publication and impact process (see, for example, HEFCE, 2015; Williams et al, 2015).…”
Section: Seeking Impact: When Safe Advice Meets Professional Dilemmasmentioning
confidence: 99%
“…Furthermore, there is insufficient focus on the factors that political scientists and policy process scholars would use to understand the role of evidence in policymaking: the ways in which policymakers address ‘bounded rationality’, and dilemmas created by a complex policymaking environment in which the discrete effect of individual action is often impossible to determine (Andrews, 2017; Cairney, 2017a, 2018b; Cairney et al, 2016; Cairney and Kwiatkowski, 2017; Cairney and Oliver, 2017; Cairney and Rummery, 2018; Cairney and Weible, 2017; Cairney and Yamazaki, 2018; Jones and Anderson Crow, 2017; Parkhurst, 2017; Sohn, 2018; Witting, 2017; Zampini, 2018).…”
Section: Studies Of the ‘Barriers’ To Academic Impact And Practical Amentioning
confidence: 99%
“…Fourth, a low tendency to define inequalities primarily with reference to gender helps explain the lack of policy coherence: low-priority issues seem relatively coherent in isolation (such as in a high-level strategy document), only to be undermined by a tendency to devote disproportionate attention and resources to other issues . Although policy-makers take gender seriously, most of their attention is focused on more general and higher profile economic and constitutional issues in which gender often plays a subordinate role (Cairney & Rummery, 2018). This limited attention undermines clarity about how to translate general mainstreaming aims into specific sectors such as education, and this uncertainty increases as we increase the number of relevant sectors (such as health, justice, transport, social work and social care).…”
Section: Step 2: Map Policy-making Responsibilitiesmentioning
confidence: 99%